Solving Radiative Transfer Equation (RTE) in Time-Dependent Mode - Ow Shen, Wah; Joe, Wong; Tan Ching, Seong (2008)
This paper covers the analytical approach in solving time-dependent radiative transfer equation (RTE) for one-dimensional (1D) slab geometry. As light passing through a turbid medium, photons exhibit two main processes that are: absorption and scattering. It is not easy to characterize the propagation of light beam in a medium due to various optical properties for different types of medium. Thus by getting the solution from the equation of radiative transfer, we are able to study the characteristic of light distribution while penetrating through the concerned medium. Several assumptions and approximation have been implicitly used to solve the radiative transfer problems in order to avoid ambiguity. In this paper, we use isotropic diffusion approximation in the radiative transfer equation (RTE) and determine the light intensity as a function of time and space.